Transformasi Pembelajaran BTQ untuk Percepatan Literasi Qur’ani di Lingkungan Madrasah Aliyah Unggulan Nur Al-Jadid Sidoarjo - Sulaiman, M. Sholehuddin; Asas, Fitria (Humanist Journal, 2025)
This article aims to transform the learning process of Qur’anic Reading and Writing (BTQ) to accelerate students’ ability to read and write the Qur'an at MA Unggulan Nur Al-Jadid Waru Sidoarjo. The method used in this study is the Asset-Based Community Development (ABCD) approach, which focuses on developing the assets and potentials found within the school environment. The program's implementation involved student-teachers from Universitas Sunan Giri Surabaya as facilitators in BTQ learning activities for grades X, XI, and XII. The activities included teaching tajwid (rules of Qur'anic recitation), memorization, and transcription of Qur’anic verses based on proper principles. The results of the study indicate that the systematic and effective application of BTQ significantly improves students' Qur’anic literacy skills. The program's success was supported by the active involvement of educators, parents, and a conducive school environment. These findings affirm the importance of BTQ as a locally integrated subject in the curriculum to strengthen students’ spiritual foundation and support their academic achievement.